Fatal meningoencephalitis in child and isolation of Naegleria fowleri from hot springs in Costa Rica - Abrahams Sandí, Elizabeth (2015)
In summary, this investigation identified an N. fowleri ameba in water sources at a resort in Costa Rica that had been visited by a child from the United States who died of PAM as a results of N. fowleri infection. These amebas pose a high risk to human health and were found in an area frequented by tourists, which should alert health authorities in Costa Rica of the need for monitoring locations such as this for possible contamination and notifying the public of the risk for infection.